2007
DOI: 10.1097/jom.0b013e3180329a8d
|View full text |Cite
|
Sign up to set email alerts
|

The PHLAME (Promoting Healthy Lifestyles: Alternative Models??? Effects) Firefighter Study: Outcomes of Two Models of Behavior Change

Abstract: Both a team-centered and individual-oriented intervention promoted healthy behaviors. The scripted team curriculum is innovative, exportable, and may enlist influences not accessed with individual formats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
230
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(240 citation statements)
references
References 42 publications
7
230
0
3
Order By: Relevance
“…The promoting healthy lifestyles (PHLAME) wellness/injury reduction program was developed, shown efficacious, and beta-tested with funding from the National Institutes of Health [11][12][13]. The PHLAME curriculum offers 12 45-min interactive sessions to be completed once per week over approximately 4 months.…”
Section: Discussionmentioning
confidence: 99%
“…The promoting healthy lifestyles (PHLAME) wellness/injury reduction program was developed, shown efficacious, and beta-tested with funding from the National Institutes of Health [11][12][13]. The PHLAME curriculum offers 12 45-min interactive sessions to be completed once per week over approximately 4 months.…”
Section: Discussionmentioning
confidence: 99%
“…Buttriss et al (22) drew special attention to one of these studies, the Treatwell 5-a-Day Study, showing that involving family members could be a promising strategy to increase fruit and vegetable intake (24) , with potential benefits for the whole family (25) . Tailored health information and different counselling opportunities were provided in two more recently published intervention studies, one among construction labourers using telephone-delivered and mailed intervention (26) and another targeting firefighters either through a team-centred curriculum or through individual motivational interviews (27) . In these cases, intervention effects of approximately 1-1.5 servings of fruit and vegetables were observed, comparable to the effect found in a study targeting solely the physical environment, making fruit and vegetables in lunch meals easily available and more appealing at worksite canteens (28,29) .…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators (Carey et al 2011;Elliot et al 2007;Winick et al 2002) have reported short-term (<6 months) beneficial effects of health promotion programs on the weight and BMI of firefighters. However, the initial program effects did not last long after the completion of the programs (MacKinnon et al 2010;Ranby et al 2011;Winick et al 2002).…”
mentioning
confidence: 99%